NATURAL ZEOLITES AS MANURE ADDITIVE: THE ADVANTAGES AND DISADVANTAGES - Lenny Marilyn Estiaty; Dewi Fatimah; Dadan Suherman; Kamaludin Alamsyah (Jurnal Zeolit Indonesia, 2005)
Research has been done to evaluate the addition of zeolite to manure fertilizer. This research is aimed to review the advantages and disadvantages of zeolites as manure fertilizer additive. Investigation is carried out by different variables: zeolite particle size, zeolite concentration and curing time. The results show that zeolite particle sizes of "“7 +10 mesh and "“20 +48 mesh did not significantly different. Zeolite "“ compost mixture can dry very fast, just in 2 weeks curing time the residual water content is only 5-6%, while that on the controlled compost (without zeolite) is still 70%. Higher zeolite concentration will speed up the compost drying process. On the other hand, zeolite addition will increase the potassium content by 1.7"“2% but it also increases NH3 volatilization, which will result in a lower N content. Higher zeolite concentration will give lower N content in the composite. It can be concluded that zeolite addition is suggested not applied to the fresh compost but just before the compost will be used in order to increase the nutrition efficiency.